The Mass Incarceration of Black Women in Brazil - Laura Marquesan Eschberger (e-cadernos ces)
Colonial empires establish their system of power based on white male supremacy across all spheres of society. In this process, incarceration systems were – and can still be – a key element in the preservation of racial, class, and gender hierarchies. In recent decades, extensive research has sought to expose how the incarceration system enjoys an intimate relationship with structural racism. In addition, the War on Drugs initiative accentuates these effects in Latin-American countries. From 2010 to 2014, the incarceration of women in Brazil increased by 567% (World Prison Brief, 2015). This paper, in applying an interdisciplinary approach, will briefly analyze the role of gender and race in this process and will point out how certain colonial legacies operate in Brazilian justice.